Plant use and perceptions in the context of sexual health among people of Congolese descent in Belgium - Laura Van Damme; Lars Chatrou; Eduardo de la Peña; Pathy Kibungu; Césarine Sinatu Bolya; Patrick Van Damme; Wouter Vanhove; Melissa Ceuterick; Emiel De Meyer (BMC, 2024)
Abstract Background The use of medicinal plants is integral to global healthcare systems, with Sub-Saharan Africa maintaining a robust tradition of herbal medicine alongside Western-oriented healthcare. As migrant communities tend to continue traditional herbal practices after migration, documenting this use is vital to develop culturally sensitive healthcare. This study investigates plant usage and perspectives in the context of sexual and reproductive health among the Congolese community in Belgium, particularly in the Matongé quarter of Brussels. Our research questions were: (1) What is the current knowledge of medicinal plants among the Congolese community in Belgium in the context of sexual health, and what are the applications and commonly employed administration methods of these plants? (2) What role does herbal medicine play in the context of sexual health for people of Congolese descent in Belgium and how this is influenced by perceptions of sexuality? and (3) Is there a gender bias in the use of medicinal plants, and if so, can this be related to perceived gender norms? Methods We conducted 22 semi-structured interviews with people of Congolese descent currently living in Belgium. Participants were selected using both snowball sampling and purposive sampling. Plant use in the context of sexual health was recorded through freelisting. Data on narratives, ideas, and perceptions of this plant use in the context of sexual health were collected. Interview transcripts were analyzed using thematic analysis. Results We identified 17 plant species used for sexual health. Three overarching themes emerged from our data. Plants were used with a notable gender bias favoring male sexual potency enhancement. Men used these plants for both remedying potency issues and enhancing sexual prowess. In contrast, knowledge about plants for female sexual health was limited. Gender norms reinforced the importance of male sexual potency, while stigmatizing open discussions of female sexuality. Conclusions The use of medicinal plants for sexual health raises health, social, and conservation concerns, underscoring the need for further research in this area. This study contributes to understanding medicinal plant use within the Congolese community in Belgium and highlights the necessity for future research on herbal practices for female sexual health in this context.